Analisis Kebutuhan (Need Analysis) dan Analisis Kurikulum Sebagai Dasar Pengembangan Bahan Ajar (Pusat riset dan Inovasi Nasional, 2026)
This article examines needs analysis and curriculum analysis as the foundational bases for developing effective teaching materials. Using a library research method, this study reviews various scientific journal articles, reference books, and relevant official documents. Needs analysis is a systematic process conducted to identify the gap between students' current conditions and the competencies they are expected to achieve, serving as the most critical stage in determining the direction of teaching material development. Meanwhile, curriculum analysis is carried out to ensure that the teaching materials developed remain aligned with competency standards, learning outcomes, content structure, and applicable educational policies. The integration of both analyses produces teaching materials that are not only contextually relevant to students' real conditions but also consistent with curriculum demands. Systematic steps in this integration including learner characteristic analysis, curriculum document review, material priority mapping, and authentic assessment design significantly contribute to improving the quality, effectiveness, and meaningfulness of learning. This article concludes that needs analysis and curriculum analysis are inseparable and must be conducted systematically before the development of teaching materials begins.